Hedgehog Signaling in the Subventricular Zone Is Required for Both the Maintenance of Stem Cells and the Migration of Newborn Neurons - Balordi, Francesca (J Neurosci, 2007)
We examined the postnatal consequences of removing Hedgehog signaling within the adult stem cell niche. Although at birth the subventricular zone appears normal in mice lacking Hedgehog signaling, by postnatal day 8 it is greatly impaired, and cell death is increased. In addition, both the quiescent B stem cell population and transit-amplifying C cells become depleted postnatally. In contrast, the A cell population expands precociously, mostly fails to migrate to the olfactory bulbs, and is ultimately also depleted by postnatal day 30. In vitro and in vivo analyses demonstrate that this failure in migration is a result of nonautonomous signaling, possibly caused by a reduction in Slit1 ligand in A cells. These results suggest that Hedgehog signaling is required for the maintenance of the B and C cell populations and indirectly for the migration of the neurons that are generated from the adult stem cell niche.